USAHATANI JERUK MENDUKUNG PENDAPATAN PETANI PADA LAHAN PASANG SURUT DI KALIMANTAN SELATAN ( Kasus di Desa Barambai Muara Kec Marabahan Kab Barito kuala) - Rismarini Zuraida (Agriekonomika, 2012)
ABSTRAKTidal land included marginal land that has high acid. One cause is management of resources is not optimum yet.This research was aimed to find out contribution of orange cultivation to the farmer income of tidal land in Barambai Muara Village Barito regency South Borneo during June and August 2010. This research was conducted by survey method through PRA (Participatory Rural Appraisal) approach. Data obtained from interviews with 25 respondents that are chosen by random sampling. Interview focus is on resource, constraint and opportunity of orange cultivation in the tidal land. Tidal land in the south Borneo has high potential to improve the farmer income. A farmer cultivate the orange plants 150 to 300, its produce net income are Rp14.520.000,-  or 71,50% of household income. Mostlypaddyis cultivated onlyonce a yearthatlocalriceproductivityreached 2.1tons/acreissufficient to meettheir daily needs. Laborlargelydevoted to the orange cultivation. The constraints of orange cultivation are limitedtechnology andlowprices. Farmers need the Government's attention especially on marketing because this area has high potential to be developed.Keywords: orange cultivation, tidal land, Participatory Rural Appraisal, household income